Analisis Parameter Kimia Kualitas Air Minum Ayam Petelur (Gallus domesticus) di Kabupaten Blitar dan Kajian Literatur Fitoremediasi Kadar Fluorida - Yulianti, Eny; Wahyuningtyas, Titian Ajeng; Sholikhah, Badiatus; Yuliastuti, Rostiwi Endah; Royanudin, Moch; Nafi’ah, Sriani (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Drinking water quality is a crucial factor that influences livestock productivity. Regular evaluation of the quality of livestock drinking water is an essential activity. Blitar Regency is known as a center for egg production from laying hens (Gallus domesticus). This study aims to evaluate the quality of livestock drinking water and provide a literature review regarding the potential for improvement through phytoremediation methods. This research method involves laboratory analysis and literature review. Laboratory analysis is carried out to determine the quality of water chemical parameters, then the results are compared with livestock drinking water standards regulated by Regulation of the Minister of Health of the Republic of Indonesia Number 32 of 2017. If a discrepancy is found with the standards, it is continued with a literature study regarding the use of phytoremediation methods as a solution. Analysis of chemical parameters, including ion levels, using a reagent kit with the help of Spectroquant Pharo 300 UV Vis spectroscopy. The results of the analysis involve iron, fluoride, manganese, nitrate, nitrite, cyanide, hardness, cadmium, zinc metal and sulfate. All parameters meet quality standards, except for Fluoride (F-) levels which exceed the threshold of 1.5 mg/L, caused by the use of groundwater sources or wells which have the potential to have higher mineral content than surface water. The potential impacts of high fluoride levels on laying hens include reduced egg production, impaired growth, reproductive disorders, decreased water consumption, and decreased body weight. The literature review highlights phytoremediation methods involving plants as an economical and effective solution. Afforestation, such as planting grass or bushes around livestock areas and wells, or through creating ponds with aquatic plants, can significantly reduce fluoride levels in livestock drinking water.